Abbreviated Gadoxetic Acid‐Enhanced MRI for the Detection of Liver Metastases in Patients With Potentially Resectable Pancreatic Ductal Adenocarcinoma. Issue 3 (10th January 2022) - Yamaguchi, Takeru; Sofue, Keitaro; Ueshima, Eisuke; Ueno, Yoshiko; Tsujita, Yushi; Yabe, Shinji; Shirakawa, Sachiyo; Toyama, Hirochika; Hori, Masatoshi; Fukumoto, Takumi; Murakami, Takamichi
Abstract : Background: Gadoxetic acid‐enhanced magnetic resonance imaging (MRI) is useful in detecting liver metastases from pancreatic ductal adenocarcinoma (PDAC). However, the long examination time limits its utility in the initial workup of patients with PDAC. Purpose: To evaluate the incremental value of an abbreviated gadoxetic acid‐enhanced MRI for the detection of liver metastases in patients with PDAC. Study Type: Retrospective. Population: Patients ( N  = 130) with potentially resectable PDAC (women, 58 [44.6%]). Field Strength/Sequence: 1.5 T and 3 T; gradient dual‐echo T1‐weighted (in‐phase and opposed‐phase), fat‐suppressed fast spin‐echo T2‐weighted, single‐shot echo‐planar diffusion‐weighted, and three‐dimensional fat‐suppressed T1‐weighted gradient‐echo dynamic contrast‐enhanced and hepatobiliary phase sequences, as well as contrast‐enhanced computed tomography (CECT). Assessment: Three radiologists independently reviewed three different image sets to detect liver metastases: set 1, CECT alone; set 2, CECT and abbreviated MRI comprising fat‐suppressed T2‐weighted, diffusion‐weighted, and hepatobiliary phase images; and set 3, CECT and standard gadoxetic acid‐enhanced MRI. Statistical Tests: Figure of merit (FOM) was compared using the jackknife alternative free‐response receiver operating characteristics, and other per‐lesion and per‐patient diagnostic parameters for each image set were compared using McNemar's and Fisher's test. P  < 0.05 was considered statistically significant. Results: A total of 43 liver metastases were identified in 13 patients. Reader‐averaged FOM to detect liver metastases were significantly higher for sets 2 (0.884) and 3 (0.886) than for set 1 (0.609), while they were comparable between sets 2 and 3 ( P  = 0.96). The mean per‐patient sensitivities, negative predictive values, and accuracies were significantly higher for sets 2 and 3 than for set 1, while those between sets 2 and 3 were not significantly different (not applicable, P  > 0.99, and P  > 0.99, respectively). Data Conclusion: Gadoxetic acid‐enhanced MRI combined with CECT had higher diagnostic performance than CECT alone for the detection of liver metastases in patients with PDAC. The incremental values were comparable for the abbreviated MRI and standard MRI. Level of Evidence: 3 Technical Efficacy: Stage 2